Corporate ownership network in the automobile industry: Owners, shareholders and passive investment funds - Mário do Sacomano Neto; Marcelo Carmo; Evandro Marcos Saidel Ribeiro; Wilton Vicente Gonçalves da Cruz (Research in Globalization, 2020)
Who controls the corporate ownership network in the automotive industry: owners, shareholders or financial institutions? Recent studies have suggested that corporate control of automotive firms is increasingly associated with banks, investment funds and other players in the financial system. In particular, investment funds have reinforced significant changes in the ownership structure of the economy in the last few years. These changes imply a significant increase in financialization and the role of financial institutions in the dynamics and behavior of firms. Thus, this paper aims to: 1) analyze the corporate ownership networks of the largest automobiles companies; 2) assess the structure and relations in the corporate ownership network; 3) identify groups in the corporate ownership network; and 4) analyze the extent to which organizations depend on financial institutions. The corporate ownership network includes the 30 largest automakers worldwide connected with the largest holders supported by social network analysis (representing 348 nodes and 654 connections, among companies, banks, investment funds, and state). The findings of this study show how the corporate ownership network in the automotive industry is strongly intermediated by passive investment funds, such as BlackRock, Vanguard Group, Dimensional and State Street, which occupy a prominent structural position. These investment funds exhibit the highest scores of weight centrality, betweenness, and eigencentrality in the network. These funds have a prominent structural position and intermediate shares like blockholders on a different stock exchange. However, we observed a notable difference from Asian companies in American corporations. Asian companies match increases in productive and financial operations, accumulating and originating funds with a lower degree of financial exposure, while American companies exhibit greater dependence on finance activities. Beyond the corporate ownership network, we explore evidence from field theory, resource dependence theory, and the sociology of arbitrage to address the automotive companies' dependence on investment funds.
Keywords: 330; Automotive industry; Corporate control; Financialization; Governance; Network analysis